Modeling growth and development of hydroponically grown dill, parsley, and watercress in response to photosynthetic daily light integral and mean daily temperature. - Kellie J Walters; Roberto G Lopez (PLoS ONE)
In controlled environments, crop models that incorporate environmental factors can be developed to optimize growth and development as well as conduct cost and/or resource use benefit analyses. The overall objective of this study was to model growth and development of dill 'Bouquet' (Anethum graveolens), parsley 'Giant of Italy' (Petroselinum crispum), and watercress (Nasturtium officinale) in response to photosynthetic daily light integral (DLI) and mean daily temperature (MDT). Plants were grown hydroponically in five greenhouse compartments with MDTs ranging from 9.7 to 27.2 °C under 0%, 30%, or 50% shade cloth to create DLIs ranging from 6.2 to 16.9 mol·m‒2·d‒1. MDT and DLI interacted to influence dill fresh mass and height, and watercress maximum quantum yield of dark adapted leaves (Fv/Fm), height, and branch number while only MDT affected dill leaf number and watercress fresh mass and branch length. Besides dry matter concentration (DMC), parsley was influenced by MDT and not DLI. Increasing MDT from ≈10 to 22.4 °C (parsley) or 27.2 °C (dill and watercress), linearly or near-linearly increased fresh mass. For dill, increasing DLI decreased fresh mass when MDT was low (9.7 to 13.9 °C) and increased fresh mass when MDT was high (18.4 to 27.2 °C). DMC of dill, parsley, and watercress increased as MDT decreased or DLI increased, indicating a higher proportion of plant fresh mass is water at higher MDTs or lower DLIs. With these data we have created growth and development models for culinary herbs to aid in predicting responses to DLI and MDT.